Remote Experiments as an Asset for Learning Programming in Python - Guerra, H. (2016)
The online experimentation is in expansion in Higher Education Institutions, with a dynamic extension to all scientific areas. The integration of online labs in higher educational courses constitutes a significant financial saving way for the institutions with multiple benefits for student's learning. Without access and usage time restrictions, these labs provide a wide range of experiments, performed individually or in groups, repeated as often as needed, without any space or time restrictions, just imposing the Internet access is available and in good conditions. This paper describes a use case application of a web platform that integrates, monitors and controls different technologies, such as Wireless Sensor Networks, Virtual Sensor Networks and Data Acquisition Boards, through an Internet accessible RESTful API, using low-cost devices such as the Raspberry Pi. In this context, a remote laboratory is developed for students programming in Python, based on such platform to improve their programming skills, overcome their difficulties in CS1 and CS2 courses, and give the ability to interact to physical world through practical examples.